2021
DOI: 10.37989/gumussagbil.790884
|View full text |Cite
|
Sign up to set email alerts
|

Preparedness Situations of Health Personnel for Disaster and Emergencies

Abstract: Afetler, öngörülemeyen bir zamanda bir toplumun günlük yaşamını olumsuz etkileyen ve genellikle sağlık hizmeti ihtiyacına yol açan olaylardır. Bu çalışmanın amacı araştırmaya katılan sağlık personellerinin afet ve acil durumlar için hazırlıklı olma durumunun, kendi görüşleri doğrultusunda değerlendirilmesidir. Bu araştırma tanımlayıcı bir çalışma olup araştırma verileri, araştırmacılar tarafından oluşturulan anket ile toplanmış ve 276 anket değerlendirilmiştir. Katılımcıların %23,2'si kimyasal, biyoloji… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 8 publications
(1 reference statement)
1
7
0
Order By: Relevance
“…When the literature on disaster awareness studies is examined, there are studies that support the findings of our study (Şahin et al, 2018;Tekin and Dikmenli, 2021) and studies that have different results from our findings (Dikmenli and Yakar, 2019; URL 1; Ozkazanc and Yuksel, 2015;Bhat et al, 2017;Avcı et al, 2020;Oyanık and Cengiz, 2020;Demirci, 2021). When the literature on disaster preparedness studies is examined, there are studies that support our findings (Aslantaş and Tabuk, 2021) and differ from our findings (Ağahan, 2018;Koçak, 2004;Tanner and Doberstein, 2015; URL 1; Ozkazanc and Yuksel, 2015;Şahin et al, 2018;Dinçer and Kumru, 2021;Hasan et al, 2022). When some studies in the literature are examined, it is understood that disaster awareness and disaster preparedness are not at a sufficient level in most of the studies applied to the general public.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…When the literature on disaster awareness studies is examined, there are studies that support the findings of our study (Şahin et al, 2018;Tekin and Dikmenli, 2021) and studies that have different results from our findings (Dikmenli and Yakar, 2019; URL 1; Ozkazanc and Yuksel, 2015;Bhat et al, 2017;Avcı et al, 2020;Oyanık and Cengiz, 2020;Demirci, 2021). When the literature on disaster preparedness studies is examined, there are studies that support our findings (Aslantaş and Tabuk, 2021) and differ from our findings (Ağahan, 2018;Koçak, 2004;Tanner and Doberstein, 2015; URL 1; Ozkazanc and Yuksel, 2015;Şahin et al, 2018;Dinçer and Kumru, 2021;Hasan et al, 2022). When some studies in the literature are examined, it is understood that disaster awareness and disaster preparedness are not at a sufficient level in most of the studies applied to the general public.…”
Section: Discussionsupporting
confidence: 54%
“…Various studies have been conducted in the literature on disaster preparedness or disaster awareness (Koçak, 2004;Scolobig et al, 2012;Donahue et al, 2014;URL 1;ChungHee et al, 2015;Ozkazanc and Yuksel, 2015;Tanner and Doberstein, 2015;Bhat et al, 2017;Ağahan, 2018;Dökmeci and Merinç, 2018;Şahin et al, 2018;Tkachuck et al, 2018;Dikmenli and Yakar, 2019;Avcı et al, 2020;Cerulli et al, 2020;Ertuğrul and Ünal, 2020;Rogayan and Dollete, 2020;Oyanık and Cengiz, 2020;Suryaratri et al, 2020;Aras et al, 2021;Tekin and Dikmenli, 2021;Türksever, 2021;Demirci, 2021;Aslantaş and Tabuk, 2021;Dinçer and Kumru, 2021;Şahan and Dinç, 2021a;2021b;Hasan et al, 2022;Bor, 2023). The hypotheses put forward for the purpose of the study are as follows:…”
Section: Introductionmentioning
confidence: 99%
“…In studies conducted in recent years, it has been determined that there are hospital disaster plan teams, but these team members do not know their du�es and responsibili�es in the hospital disaster plan, that Emergency Health service employees find the disaster drills and disaster training insufficient and they have insufficient knowledge in responding to disasters (Dinçer & Kumru, 2021;Kaynak & Kutlu, 2023;Pamuk Cebeci & Arberk, 2021). Contrary to these studies, in some studies, it was found that the disaster training and disaster preparedness levels of the hospital disaster team were at an acceptable level, and the employees' knowledge about the hospital disaster plan was at a mediumhigh level (Sarık & Cengiz, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, supporting the curriculum with disaster trainings in primary and secondary education and higher education will both increase awareness and minimize losses (Şengün and Küçükşen;2019: 194) (YÖK atlas, 2023). Considering the studies conducted in our country on the preparedness of healthcare personnel for disasters, it is seen that employees such as nurses, physicians, midwives, health technicians are generally included in the research (Dinçer & Kumru, 2021;Yıldırım & Gerdan, 2017;Çelebi & Uçku, 2017;Sezer et al, 2013;Gündüz & Akyüz, 2022). However, considering the institutions where graduates of the department of health management will work, it is foreseen that they can also take part in disaster management phases such as disaster response and emergency planning.…”
Section: Introductionmentioning
confidence: 99%